Outcomes of Immunocompromised Adults Hospitalized With Laboratory-confirmed Influenza in the United States, 2011–2015. (11th July 2019) - Collins, Jennifer P; Campbell, Angela P; Openo, Kyle; Farley, Monica M; Cummings, Charisse Nitura; Hill, Mary; Schaffner, William; Lindegren, Mary Lou; Thomas, Ann; Billing, Laurie; Bennett, Nancy; Spina, Nancy; et al.
Abstract: Background: Hospitalized immunocompromised (IC) adults with influenza may have worse outcomes than hospitalized non-IC adults. Methods: We identified adults hospitalized with laboratory-confirmed influenza during 2011–2015 seasons through CDC's Influenza Hospitalization Surveillance Network. IC patients had human immunodefiency virus (HIV)/AIDS, cancer, stem cell or organ transplantation, nonsteroid immunosuppressive therapy, immunoglobulin deficiency, asplenia, and/or other rare conditions. We compared demographic and clinical characteristics of IC and non-IC adults using descriptive statistics. Multivariable logistic regression and Cox proportional hazards models controlled for confounding by patient demographic characteristics, pre-existing medical conditions, influenza vaccination, and other factors. Results: Among 35 348 adults, 3633 (10%) were IC; cancer (44%), nonsteroid immunosuppressive therapy (44%), and HIV (18%) were most common. IC patients were more likely than non-IC patients to have received influenza vaccination (53% vs 46%; P < .001), and ~85% of both groups received antivirals. In multivariable analysis, IC adults had higher mortality (adjusted odds ratio [aOR], 1.46; 95% confidence interval [CI], 1.20–1.76). Intensive care was more likely among IC patients 65–79 years (aOR, 1.25; 95% CI, 1.06–1.48) and those >80 years (aOR, 1.35; 95% CI, 1.06–1.73) compared with non-IC patients in those age groups. IC patients were hospitalized longer (adjusted hazard ratio of discharge, 0.86; 95% CI, .83–.88) and more likely to require mechanical ventilation (aOR, 1.19; 95% CI, 1.05–1.36). Conclusions: Substantial morbidity and mortality occurred among IC adults hospitalized with influenza. Influenza vaccination and antiviral administration could be increased in both IC and non-IC adults. Abstract : In this cross-sectional study in 35 348 adults hospitalized with laboratory-confirmed influenza in the United States over 4 seasons, immunocompromised adults generally had worse outcomes than nonimmunocompromised adults, including higher mortality, longer hospitalizations, and higher rates of Intensive Care Units admission among older adults.